Osteocartilaginous Choriostoma of Palatine Tonsil: a Rare Hidden Entity - Shilpa Bairwa; Bhawna Sethi; Pawan Singh; Ashok Sangwaiya; Shivani Kalhan (Iranian Society of Pathology, 2018)
A choriostoma is an aggregate of microscopically normal cells or tissues which occurs in an aberrant location. It follows a benign course, rarely seen in head and neck region. A choriostoma of the palatine tonsil is very rare; less than 10 cases were reported till date. A 11-year-old male referred to ENT OPD with chronic tonsillitis and underwent tonsillectomy. The histopathological examination revealed the unexpected presence of cartilage and bone in both tonsils.